Effect of Steam Explosion and Ionic Liquid Pretreatment Technology on the Enzymatic Hydrolysis of Corn Stalk - Chen, X.; Ning, X.Q.; Zhang, B.B.; Wang, Y.L.; Zeng, G.M.; Hu, C.B. (Asian Journal of Chemistry, 2011)
The enzymatic hydrolysis of corn stalk could be increased via the methods of steam explosion and ionic liquid (IL)[Bmim]Cl as a pretreatment step. The corn stalk was enzymatic hydrolyzed for 24 h, the experimental results revealed that the yield of reducing sugars from corn stalk treated with a steam pressure of 2.6 MPa for 90 sec and combined with [Bmim]Cl treatment can reach 961.66 mg/g (dry sample). Steam explosion can also enhance the content of cellulose in the corn stalk and make the ionic liquid treatment efficient. The corn stalk treated was characterized by FTIR, XRD and SEM and the results showed that the crystallinity of corn stalk was changed from crystalline to amorphous pattern.